Self compacting concrete containing polypropylene fibre and its behaviour as wall panel under cyclic load - Khalaf Al-Alwani, Anas Qasim (2018)
Self-compacting concrete, SCC, is a new innovation of high strength concrete which uses less aggregate, able to flow by itself and does not require compaction. These advantages make it the main choice as precast system which could speed up the construction time with less wastage at the construction site. This research investigated the fresh and mechanical properties of SCC incorporating polypropylene fibre, PPF, and the structural behaviour of precast SCC panel, PSCC, with added PPF subjected to lateral cyclic load. The PSCC panel with dimensions of 2000 mm height, 1000 mm width, and 150 mm thick was tested under lateral cyclic load to study its structural behaviour according to code ACI 318 and ASCE/SEI. A parametric study was conducted on PSCC panels with various slenderness ratios, aspect ratios, and reinforcement areas to study their effects on the panel’s structural behaviour by means of finite element method using ABAQUS software, which was validated with the results from experimental work. The results showed that with optimum percentage of 0.05% PPF, SCC mixture showed good consistency and workability. The mechanical properties of SCC was noticed to increase with increased PPF where its mean compressive strength, tensile strength, modulus of elasticity and flexural strength were enhanced by 6%, 27%, 8% and 18%, respectively. It was also noticeable that PPF managed to control the crack propagation while under flexure through minimise the cracks. Under lateral cyclic load, PSCC wall achieved drift levels in increment of 2.1% with no damage appeared before failure. The damage of the wall at failure was limited to its base region due to critical stresses concentrated within this area. It was also noticed that PSCC wall with added PPF achieved higher drift with higher dissipation energy up to 3000 kJ at 2.7 % compared to Ruiz, et al wall’s which achieved dissipation energy of 700 kJ at 1.3 % drift. Maximum strains recorded on the surface of panel and in the steel reinforcement were observed at the base region which confirms the crack and crush occurred within this region. Higher slenderness ratio of panel recorded lower ultimate load but higher maximum horizontal displacement and more ductile behavior. Meanwhile, aspect ratio showed the opposite results where lower aspect ratio resulted with higher ultimate load achieved but smaller maximum displacement, where wall behaved in a less ductile behaviour. Higher the reinforcement area recorded higher ultimate load and maximum displacement. However, it is noticed that the reinforcement area did not have any significant effect on the ductility behavior of the panel.